2018
DOI: 10.3390/aerospace5020064
|View full text |Cite
|
Sign up to set email alerts
|

ReDSHIFT: A Global Approach to Space Debris Mitigation

Abstract: The H2020 ReDSHIFT project aims at finding passive means to mitigate the proliferation of space debris. This goal is pursued by a twofold research activity based on theoretical astrodynamics, computer simulations and the analysis of legal aspects of space debris, coupled with an experimental activity on advanced additive manufacturing (3D printing) applied to the production of a novel small satellite. Several different aspects related to the design and production of a debris compliant spacecraft are treated, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…One of the goals of the ReDSHIFT is the development of a software toolkit that would enable an informed design of "debris compliant" missions, including the design of an appropriate passive removal strategy, given an operational orbit and ∆V budget. We refer the reader to Rossi et al (2018) for a in-depth discussion about the software toolkit. The results presented in this paper have been collected in the form of a database of pre-computed solutions, to be used as input in the software toolkit.…”
Section: Gnss-graveyard Studymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the goals of the ReDSHIFT is the development of a software toolkit that would enable an informed design of "debris compliant" missions, including the design of an appropriate passive removal strategy, given an operational orbit and ∆V budget. We refer the reader to Rossi et al (2018) for a in-depth discussion about the software toolkit. The results presented in this paper have been collected in the form of a database of pre-computed solutions, to be used as input in the software toolkit.…”
Section: Gnss-graveyard Studymentioning
confidence: 99%
“…Our study is part of the EC-funded "ReDSHIFT" project 1 (Rossi et al, 2018). The main goal of this project is to introduce a holistic approach in the design of passive debris removal strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is demonstrated that there exists an integral of motion, corresponding to (β cos i − α) µa(1 − e 2 ) = constant, (6) where α, β are as defined in Eq. (2). In other words, assuming that the motion of the spacecraft is governed only by the Earth's monopole, the Earth's oblateness and the solar radiation pressure, at any instant we can recover the inclination value from…”
Section: Analysis In the Frequency Domainmentioning
confidence: 99%
“…Past numerical simulations have shown that some geostationary transfer orbits (GTOs) are dynamically shortlived (Janin 1991;Siebold and Reynolds 1995;Morand et al 2012), and recent works have demonstrated that this problem still presents a number of interesting and hitherto unknown features Gurfil 2016, 2017). Motivated by our preceding dynamical survey of orbital stability and associated lifetimes in circumterrestrial spacefrom low-Earth orbit (LEO) to beyond the geostationary ring (GEO) (Rosengren et al 2018) -conducted in the framework of the ReDSHIFT project (Rossi et al 2017(Rossi et al , 2018, we revisit the problem of GTO long-term stability. In fact, we extend our previous results, based solely on the long-term conservative evolution, by adding the effect of atmospheric drag at high altitudes.…”
Section: Introductionmentioning
confidence: 99%